Surface dynamics, equilibrium points and individual lobes of the Kuiper Belt object (486958) Arrokoth - Amarante, A. [UNESP]; Winter, O. C. [UNESP] (Oxford University Press (OUP), 2020)
The New Horizons space probe led the first close flyby of one of the most primordial and distant objects left over from the formation of the Solar system, the contact binary Kuiper Belt object (486958) Arrokoth. This is composed of two progenitors, the lobes called Ultima and Thule. In the current work, we investigate Arrokoth's surface in detail to identify the location of equilibrium points and also we explore each lobe's individual dynamic features. We assume that Arrokoth's irregular shape is a homogeneous polyhedra contact binary. We explore its dynamic characteristics numerically by computing its irregular binary geopotential in order to study its quantities, such as geometric height, oblateness, ellipticity and zero-power curves. The stability of Arrokoth Hill was also explored through zero-velocity curves. Arrokoth's external equilibrium points have no radial symmetry due to its highly irregular shape. We identified even equilibrium points concerning its shape and spin rate: i.e. four unstable external equilibrium points and three inner equilibrium points, where two points are linearly stable, with an unstable central point that has a slight offset from its centroid. Moreover, the large and small lobes each have five equilibrium points with different topological structures from those found in Arrokoth. Our results also indicate that the equatorial region of Arrokoth's lobes is an unstable area due to the high rotation period, while its polar locations are stable resting sites for surface particles. Finally, the zero-power curves indicate the locations around Arrokoth where massless particles experience enhancing and receding orbital energy.
Keywords: Celestial mechanics; Kuiper belt objects: individual: (486958) Arrokoth; Methods: numerical; Software: development; Software: simulations